Self-assembly and anti-amyloid cytotoxicity activity of amyloid beta peptide derivatives - Castelletto, V. (2017)
The self-assembly of two derivatives of KLVFF, a fragment Aβ(16-20) of the amyloid beta (Aβ) peptide, is investigated and recovery of viability of neuroblastoma cells exposed to Aβ (1-42) is observed at sub-stoichiometric peptide concentrations. Fluorescence assays show that NH 2 -KLVFF-CONH 2 undergoes hydrophobic collapse and amyloid formation at the same critical aggregation concentration (cac). In contrast, NH 2 -K(Boc)LVFF-CONH 2 undergoes hydrophobic collapse at a low concentration, followed by amyloid formation at a higher cac. These findings are supported by the β-sheet features observed by FTIR. Electrospray ionization mass spectrometry indicates that NH 2 -K(Boc)LVFF-CONH 2 forms a significant population of oligomeric species above the cac. Cryo-TEM, used together with SAXS to determine fibril dimensions, shows that the length and degree of twisting of peptide fibrils seem to be influenced by the net peptide charge. Grazing incidence X-ray scattering from thin peptide films shows features of β-sheet ordering for both peptides, along with evidence for lamellar ordering of NH 2 -KLVFF-CONH 2. This work provides a comprehensive picture of the aggregation properties of these two KLVFF derivatives and shows their utility, in unaggregated form, in restoring the viability of neuroblastoma cells against Aβ-induced toxicity.